الوزارة الدينية 2020 KSKK تحليل كتاب تعليم اللغة العربية للفصل العاشر - Salsabilla Vatiha Azsira; Rahmawati Rahmawati; Fauzana Annova (Journal Cerdas Mahasiswa, 2022)
Arabic language teaching book for class 10 written by Muhammad Elias and published by KSKK (Kurikulum, Sarana, Keleembagaan, Kesiswaan) School Directorate, this book is the first volume to be printed in 2020, this textbook in Arabic for class 10 contains materials that will be taught to students, starting from The skill of listening, reading, speaking and writing, also equipped with translation instructions from Arabic into Indonesian. The main issue in this research: How was the condition of the Arabic language textbook for the tenth semester KSKK Religious Ministry 2020, and the desired purposes of this research are to know the order of presentation of materials in the Arabic textbook KSKK Religious Ministry 2020. And to find out the appropriateness of the materials with indicators in the Religious Ministry Resolution 183 in In 2019. As for this research, it is qualitative research. The research method used in this research is qualitative analysis. As for tools, including: desk study and documentary study. As for the result of this research, the order of displaying materials in the Arabic textbook KSKK Religious Ministry 2020. I mean, in the KSKK Religious Ministry 2020 Arabic textbook, there are six lessons, in each lesson consists of basic competency, indicators, Concept maps and then arrange the materials starting with listening, reading, grammar, speaking, writing and summarizing. In each lesson there are exercises. Adequacy of the materials in the Arabic language teaching book for the tenth chapter KSKK Religious Ministry 2020 There is a contradiction between the materials that are not appropriate with indicators, then all the skill in the chapter is a difference between them. I mean in the Arabic language education book KSKK Religious Ministry 2020 the skill starts from listening, reading, grammar, speaking and writing, while the Ministry’s decision Religious 183 in 2019 which starts from listening, speaking, reading and writing.